ANALISIS PENERAPAN METODE ACTIVITY BASED COSTING DALAM MENENTUKAN HARGA POKOK KAMAR HOTEL PADA HOTEL XYZ (SALAH SATU HOTEL DI KOTA PONTIANAK) - Chandra, Chandra (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2019)
This research is based on the background of increasing hospitality services business competition, and to win this competition, is influenced by three factors, one of which is the selling price. The selling price is the sum between Cost or Cost of Goods Sold (HPP) with a Mark up or percentage of the desired profit. Cost of Goods Sold is all costs incurred to obtain goods sold or the cost of goods sold. When an entity can manage costs incurred effectively and efficiently, it can increase the number of visitors and increase company profits. The research method used is descriptive qualitative method, which is to explain the phenomenon or event being studied. The results of the study are known that Â the calculation of the cost of the room by using ABC has a difference with the basic price determined by the management of XYZ Hotel. This difference is caused by differences in the overhead costs for each type of room contained in XYZ Hotels. In calculations determined by the management of XYZ Hotel, overhead costs are not included in the calculation of the cost of the room and are only charged to one type of cost driver.Keywords : Cost of Good Solds, Activity Based Costing, Hotel, Activity, Cost Driver.